The Expressive Value of The Segmental Phonemes: The Ayahs Describing The Battle of Uhud As A Model - Albar, Raweh Hamid; Babssal, Aisha Saleh (Arab Journal for Sciences and Research Publishing, 2021)
This study aims to explore the expressive value of the segmental phonemes in the verses describing the Battle of Uhud. These verses discuss some scenes of war and its doctrines, which provides the verses with meanings of strength and intensity. This research attempts to discover the effect of the features of segmental phonemes present on those meanings, and to indicate their connection to the general context, and that is through stating the expressive value of the features of phenomes in expressing meanings. In order to achieve this, two topics were addressed, the first: a description of the concept of strength and weakness of phonemes, the second; the expressive value of the segmental phonemes in the verses, and a descriptive approach was adopted for this study.
Keywords: Speech sounds; Consonants; Characteristics of sound; Weak sound; Battle of Uhud